Migration and Remittance Trends 2009 : A Better-Than-Expected Outcome So Far, But Significant Risks Ahead - Ratha, Dilip; Mohapatra, Sanket; Silwal, Ani (World Bank, Washington, DC, 2012)
Newly available data show that officially recorded remittance flows to developing countries reached $338 billion in 2008, higher than our previous estimate of $328 billion. Based on monthly and quarterly data released by some central banks and in line with the World Bank's global economic outlook we estimate that remittance flows to developing countries will fall to $317 billion in 2009. This 6.1 percent decline is smaller than our earlier expectation of a 7.3 percent fall. While new migration flows have fallen, existing migrants are not returning even though the job market has been weak in many destination countries. We maintain our expectation of a recovery in migration and remittance flows in 2010 and 2011, but the recovery is likely to be shallow. In all the regions, remittance flows are likely to face three downside risks: a jobless economic recovery, tighter immigration controls, and unpredictable exchange rate movements. Despite these risks, remittances are expected to remain more resilient than private capital flows and will become even more important as a source of external financing in many developing countries. Policy responses should involve efforts to facilitate migration and remittances, to make these flows cheaper, safer and more productive for both the sending and the receiving countries.